Sustainable eco-culture tourism in Royal Belum-Temenggor: emerging prospects and challenges for Orang Asli - Kamarudin, Khairul Hisyam (2014)
First part of this paper provides an overview of the concept of sustainable eco-culture tourism (ECT) including the highlight of three main pillars of sustainable ECT namely; natural and cultural resources, local host community and tourist. The discussion also looks further into the main principles of sustainable ECT. Second part of the paper will explain the process undertaken in conducting a fieldwork and survey of local communities in two selected villages namely Kampung Semelor (Temenggor) and Kampung Sungai Tiang (Royal Belum) conducted in June 2014 to identify possible prospects and/or potentials of ECT project for sustainable development and conservation of biodiversity of Royal Belum-Temenggor Forest Complex (RBTFC). Initial findings indicate a positive response from local communities regarding ECT project especially on economic and social prospects. These include income generation potential, new jobs creation in tourism and tourism-related sectors, wider engagement in training programs and promoting local traditional culture and local ‘forest-water-based’ activities for tourism. Some challenges during ECT project also highlight some issues on poverty, unsolved conflict between people and wildlife and the contest for resources among members of a growing community. The paper concludes with brief outlook on the development ECT project in the rich mega biodiversity area of RBTFC.